Catharine H. Roehrig, Renee Dreyfus y Cathleen A. Keller (eds.), Hatshepsut: From Queen to Pharaoh, New York, The Metropolitan Museum of New York Series– New Heaven and London, Yale University Press, 2005, pp. xv + 340. Con mapas, planos, fotos a color y en blanco y negro, apéndice y glosario. U$S 65,00. ISBN 0-300-11139-8 - Pietrosanti, Luca (2006)
Fil: Pietrosanti, Luca. Pontificia Universidad Católica Argentina; Argentina